Digital book for assessment and evaluation courses based on Kvisoft-kelase asynchronous pattern - Dewa Gede Hendra Divayana; Nyoman Santiyadnya; I Gede Ratnaya; I Gede Sudirtha; Suratmin Suratmin; I Putu Darmayasa (Universitas Ahmad Dahlan, 2019)
This study was conducted with the aim of obtaining information about the design of assessment and evaluation digital book as well as deployment process of the digital book through asynchronous patterns. This study uses development method with the 4D design which focuses only on define and design phase. Parties involved in conducting design trial consist of two experts namely expert of education evaluation and expert of informatics engineering education, with a trial tool in the form of questionnaires. The technique was used to analyze the trial results data from those experts was descriptive quantitative with descriptive percentages calculation. In this research, the design result of assessment and evaluation digital book with Kvisoft Flipbook Maker and the initial design of deployment with an kelase asynchronous pattern are included in the good category with a percentages of 89.38% based on experts review.